خیبر پختونخواکی مطلقہ خواتین کے حقوق و فرائض کا اسلامی تعلیمات کی روشنی میں تجزیاتی مطالعہAn Analytical Study of the Rights and Duties of Divorced Women in Khyber Pakhtunkhwa in the Light of Islamic Teachings (Al-Qamar, 2021)
The condition/plights of divorced women in KPK is that after announcing divorce the man become free himself but he do not think that how a divorced woman can sustain this fact and situation. After divorce in Islam, she obtains her vested rights along with graduation, while some duties are also given to women and after completion of these duties/rights, can live pleasant life. But in KPK the situation is opposite/contrary to Islamic teachings, on one hand the divorced was announced to a woman and on other hand the “Iddat” was completed by her in her parents’ house. She also deprived from her maintenance and her legal right. The expenses of children were also put on the shoulders of divorced woman or in some cases the custody of minor children were also been taken away from them which is unjust, unfair and beyond the teachings of Islam.
Keywords: Khyber Pakhtunkhwa; Islam; divorced women; rights